How Far From the Metaphor? The Diverse Understandings of Technical Debt in GitHub Issues - Cavalcante, Iury; Santos, Paulo Sergio Medeiros dos (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de Software, 2025)
This study investigates how the metaphor of technical debt (TD) is used in practice to communicate complex aspects of software development, particularly in relation to quality-delivery trade-offs. The study addresses the problem of inadequate or inconsistent application of the TD concept, sometimes compounded by linguistic, cultural, and organizational factors that hinder effective communication and compromise project sustainability. A qualitative analysis of issues from GitHub repositories was conducted using the Qualitative Data Analysis method. The findings revealed four main categories of TD interpretation: Decision, Activity, Problem and Pending Task. These categories encompass eight usage contexts. Many of the observed interpretations diverge significantly from the original metaphor, reinforcing the need for clearer conceptual alignment to support technical debt management practices.